Molecular Identification and Detection of Virulence Genes Among Pseudomonas Aeruginosa Isolated from Burns Infections - Polse, Reem; Khalid, Haval; Mero, Wijdan (Journal of Contemporary Medical Sciences, 2024)
Objective: Virulence factors are substances produced by pathogenic Pseudomonas aeruginosa that contribute significantly to the etiology of disease. These virulence factors are encoded by virulence genes found on the Pseudomonas aeruginosa chromosome. Methods: Between July 2021 and June 2022, 71 Pseudomonas aeruginosa isolates were identified from burn wounds at the Burn and Plastic Surgery Hospital in Duhok, Iraq. The lasB and toxA genes were identified using Polymerase Chain Reaction (PCR). Results: Only 26.36% (29/71) of the 71 Pseudomonas aeruginosa isolates were found in males, whereas 38.18% (42/71) were found in females. Furthermore, 76.06% (54/71) of the isolates were multidrug resistant. They demonstrated greater resistance to piperacillin, 98.59% resistance rates. Among the isolates analyzed, 35 (64.81%) were positive for toxA and 27 (50%) were positive for lasB genes. Conclusion: Due to the limited number of effective medications against this bacteria that are currently available, all isolates must undergo antimicrobial susceptibility testing. By doing this, you can help manage the treatment plan and stop the emergence of resistance in burn units.